Intrinsic Defects in B Cell Development and Differentiation, T Cell Exhaustion and Altered Unconventional T Cell Generation Characterize Human Adenosine Deaminase Type 2 Deficiency - Yap, Jin Yan; Moens, Leen; Lin, Ming-Wei; Kane, Alisa; Kelleher, Anthony; Toong, Catherine; Wu, Kathy H.C.; Sewell, William A.; Phan, Tri Giang; Hollway, Georgina E.; Enthoven, Karen; Gray, Paul E.; et al. (Journal of clinical immunology, 2021)
Purpose Deficiency of adenosine deaminase type 2 (ADA2) (DADA2) is a rare inborn error of immunity caused by deleterious biallelic mutations in ADA2 . Clinical manifestations are diverse, ranging from severe vasculopathy with lacunar strokes to immunodeficiency with viral infections, hypogammaglobulinemia and bone marrow failure. Limited data are available on the phenotype and function of leukocytes from DADA2 patients. The aim of this study was to perform in-depth immunophenotyping and functional analysis of the impact of DADA2 on human lymphocytes. Methods In-depth immunophenotyping and functional analyses were performed on ten patients with confirmed DADA2 and compared to heterozygous carriers of pathogenic ADA2 mutations and normal healthy controls. Results The median age of the patients was 10 years (mean 20.7 years, range 1–44 years). Four out of ten patients were on treatment with steroids and/or etanercept or other immunosuppressives. We confirmed a defect in terminal B cell differentiation in DADA2 and reveal a block in B cell development in the bone marrow at the pro-B to pre-B cell stage. We also show impaired differentiation of CD4 + and CD8 + memory T cells, accelerated exhaustion/senescence, and impaired survival and granzyme production by ADA2 deficient CD8 + T cells. Unconventional T cells (i.e. iNKT, MAIT, Vδ2 + γδT) were diminished whereas pro-inflammatory monocytes and CD56 brigh t immature NK cells were increased. Expression of the IFN-induced lectin SIGLEC1 was increased on all monocyte subsets in DADA2 patients compared to healthy donors. Interestingly, the phenotype and function of lymphocytes from healthy heterozygous carriers were often intermediate to that of healthy donors and ADA2-deficient patients. Conclusion Extended immunophenotyping in DADA2 patients shows a complex immunophenotype. Our findings provide insight into the cellular mechanisms underlying some of the complex and heterogenous clinical features of DADA2. More research is needed to design targeted therapy to prevent viral infections in these patients with excessive inflammation as the overarching phenotype.